(untitled) - Zhigarev, A. (Moskva, 1975)
This book, primarily intended for university students studying the "Electron optics and electron-beam devices" course, presents the fundamentals of electron optics including intensive-beam optics and detailed description of basic compoments of electron-beam devices as well as the most common types of such devices.
Keywords: Electron beams,Electron optics,Chùm điện tử,Quang điện tử